Projeto e desenvolvimento de câmara escura para medidas de emissão de bioluminescência ultrafraca - Marchi, Fernando (2017)
In this work it is present the design and construction of a dark chamber for the study and the realization of experiments based on the ultra-low emission of photons from biological samples that has been shown to be a promising field of research in areas such as agriculture, environment and biomedicine, whose studies of photo emissions have been proving to be an efficient way to indicate the environmental conditions through the analysis of the biological samples, becoming an alternative of low cost analysis and noninvasive diagnosis. The mechanical development of the chamber for easy operation, with dimensions sufficient to accommodate a petri dish inside, integration of a light stimulation system using illuminator ring with fiber optic and external light source, assembly of a mobile support system for selection of up to seven quartz optical filters to perform spectral analysis triggered by a stepper motor and controlled by an AVR microcontroller receiving and sending commands via serial/USB interface to a personal computer. The system uses virtual instrumentation in LabVIEW and is integrated with NI data acquisition module myDAQ, allowing integration between the different devices. Assembling a heating and cooling system of the PMT module in the chamber to maintain the biological samples at physiological temperatures and decrease the temperature of the PMT module respectively.